The impact of artificial intelligence on the stakeholder theory: A bibliometric review analysis - Figueiredo, João Maria Pereira Cunha (2024)
As Artificial Intelligence starts flourishing in this new decade it is important to understand the impact that it has in various subjects and well-known theories that were developed during the last century, more precisely, the Stakeholder Theory. The study's objectives are to pinpoint gaps in the literature and outline potential future research avenues in this rapidly developing field. Methodologically, the Elsevier Scopus platform was used to carry out an extensive screening of academic publications and the VOSviewer application was used to scrutinize the selected academic publications. Important conclusions point to a fragmented field that requires further integrative research to fully explore the complex relationships between AI and stakeholder dynamics. Furthermore, the paper highlights the value of multidisciplinary cooperation and the impact of AI on organisational goals, stakeholder relationships, and social ramifications.